Mediatization and Cultural Change in Nepal - Dhungana, Jivan (Interdisciplinary Journal of Management and Social Sciences, 2023)
Mediatization is a process of media-influence on society. In this process, people are exposed to types of media and as a result culture, politics, business, sport, education, and other parts of a society undergo change. We can see the massive utilization of social media apps by people in the present globalized context, and Nepal is also following the similar trend. Increasing use of social media apps by people of all walks of life has brought a drastic change in the way of life of Nepali people. The audio-visual effect of media is more remarkable since the use of audio-visual instruments can be clearly visualized during the feasts, rituals and celebration of festivals. People celebrate culture because culture is always important to them, but the diffusion of culture in the present has become instant caused by media. Media of course is a catalyst of macro level change and political transformation, but in case of Nepal it has become a major part of cultural transformation. The problem therefore lies on whether mediatization as a process contributes in general to positive changes or jeopardizes cultural practices in particular. It is because the contents of television, radio, newspaper, movie, music-video, online portal, meeting, school, university, social organization, civil society, etc., are less relevant to public, mediatization has become the agent to mystify culture. This paper recommends the proper utilization of media so as to enrich Nepali culture.